Biopolymers: Multidimensional Vascularized Polymers using Degradable Sacrificial Templates (Adv. Funct. Mater. 7/2015). (February 2015) - Gergely, Ryan C. R.; Pety, Stephen J.; Krull, Brett P.; Patrick, Jason F.; Doan, Thu Q.; Coppola, Anthony M.; Thakre, Piyush R.; Sottos, Nancy R.; Moore, Jeffrey S.; White, Scott R.
Abstract : S. R. White and co‐workers develop sacrificial templates of 0D to 3D used to create vascular and porous architectures in polymers on page 1043. Embedded sacrificial templates are removed using a thermal treatment process, VaSC, leaving behind an inverse replica. This reconstruction of microCT imaging shows 3D channel architecture created using a 3D printed sacrificial template and the pressure distribution of fluid flow.